Current perspectives and trends of neutrophil extracellular traps in organ fibrosis: a bibliometric and visualization study - Li, Yanbo; Cao, Zhengmin; Liu, Jing; Qiang, Rui; Wang, Jiuchong; Lyu, Wenliang (Frontiers in Immunology, 2025)
New insights into the role of immune responses in the fibrosis process provide valuable considerations for the treatment of organ fibrotic diseases. Neutrophil extracellular traps (NETs) represent a novel understanding of neutrophil functions, and their involvement in organ fibrotic diseases has garnered widespread attention in recent years. This study aims to conduct a bibliometric analysis and literature review focusing on the mechanisms by which NETs participate in fibrotic diseases. Specifically, we utilized a bibliometric dataset that includes 220 papers published in 139 journals, originating from 425 organizations across 39 countries, with a total citation count of 12,301. Keyword co-occurrence analysis indicates that the research focus on the mechanisms of NETs in organ fibrosis is likely to center on NETosis, immune responses, immune thrombosis, inflammation, and tissue damage associated with NET formation. In conclusion, our findings underscore the current status and emerging trends in NET research related to organ fibrosis, offering novel insights into the mechanisms by which NETs contribute to the pathogenesis of fibrotic diseases, as well as potential therapeutic strategies.